2014
DOI: 10.1093/occmed/kqu154
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in respiratory symptoms among cement workers: a follow-up study

Abstract: The prevalence of respiratory symptoms among cement workers was reduced after 1 year of follow-up following an intervention campaign to improve use of personal protective equipment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
5
7
1
Order By: Relevance
“…A study in the cement industry of Central Ethiopia found that workers had a significantly increased likelihood of 1.2 of having chronic respiratory diseases due to not attending OSH training (Mekasha et al, 2018). Not attending training on OSH regarding exposure to respirable dust caused a 2.73 times greater likelihood of developing chronic respiratory symptoms among cement workers (Gizaw et al, 2016), which is consistent with other studies (Ahmed Shafik and Abd El-Mohsen, 2012;Tungu et al, 2014).…”
Section: Hazard Quotient (Hq)supporting
confidence: 85%
See 1 more Smart Citation
“…A study in the cement industry of Central Ethiopia found that workers had a significantly increased likelihood of 1.2 of having chronic respiratory diseases due to not attending OSH training (Mekasha et al, 2018). Not attending training on OSH regarding exposure to respirable dust caused a 2.73 times greater likelihood of developing chronic respiratory symptoms among cement workers (Gizaw et al, 2016), which is consistent with other studies (Ahmed Shafik and Abd El-Mohsen, 2012;Tungu et al, 2014).…”
Section: Hazard Quotient (Hq)supporting
confidence: 85%
“…The use of personal respiratory protection was found to decrease the respiratory health prevalence of cement workers from 65% to 35% (Nordby et al, 2011). Moreover, several studies have found that respiratory health performance has a significant relationship with the effectiveness of PPE (Merenu et al, 2007;Zeleke et al, 2010;Tungu et al, 2014). The risk of exposure to respirable Si, As, and Cr (VI) cement dust can be reduced by 70-86% with the implementation of engineering controls (Lahiri et al, 2005).…”
Section: Hazard Quotient (Hq)mentioning
confidence: 99%
“…In 2015, a 1-year follow-up of respiratory symptoms among 134 Tanzanian cement production workers and 63 controls detected significantly lower prevalence of cough, cough with sputum, dyspnoea and wheeze among exposed workers assessed before and after a campaign promoting the use of personal respiratory protection equipment. 29 There were no changes in symptom prevalence among the controls and total dust exposure levels among exposed workers did not differ between the two time points. In a recent prospective study, we report results from a 4-year follow-up of 4966 employees of 24 cement production plants in 8 countries.…”
Section: Resultsmentioning
confidence: 81%
“…Interestingly, a Tanzanian study from 2015 showed a lower prevalence of respiratory symptoms among exposed workers assessed before and after a campaign promoting the use of personal respiratory protection equipment. 29 That study is important because it assessed the effects of an intervention. It did not, however, include lung function measurements; hence, it is not clear whether improvements in workers' lung function were achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Tungu et al [24] assessed the prevalence of respiratory symptoms among the 134 exposed workers after 1 year of follow-up following an intervention campaign to improve use of personal protective equipment. They noticed that the prevalence of pulmonary symptoms significantly decreased in the intervention group compared to the previous year [24].…”
Section: Resultsmentioning
confidence: 99%